2017
DOI: 10.1007/s00705-017-3529-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of atypical antigenic variants of canine rabies virus reveals its reintroduction by wildlife vectors in southeastern Mexico

Abstract: Rabies is an infectious viral disease that is practically always fatal following the onset of clinical signs. In Mexico, the last case of human rabies transmitted by dogs was reported in 2006 and canine rabies has declined significantly due to vaccination campaigns implemented in the country. Here we report on the molecular characterization of six rabies virus strains found in Yucatan and Chiapas, remarkably, four of them showed an atypical reaction pattern when antigenic characterization with a reduced panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…This implies that any rabies control effort in this region should consider wildlife reservoirs as a potential source of host switching and vice versa, i.e. that if the reservoir in dogs is not eliminated by sufficient population immunity, there is the risk of establishment of a subsequent wildlife RABV reservoir as observed in Mexico ( Garces-Ayala et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that any rabies control effort in this region should consider wildlife reservoirs as a potential source of host switching and vice versa, i.e. that if the reservoir in dogs is not eliminated by sufficient population immunity, there is the risk of establishment of a subsequent wildlife RABV reservoir as observed in Mexico ( Garces-Ayala et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the feline case, the V8 antigenic variant (SCSK RVV in the US) was determined and confirmed to be transmitted by a vampire bat (Desmodus rotundus), whereas the canine case corresponded to an atypical antigenic RVV from wildlife thought to be transmitted by skunks. 12 Regarding wildlife, 4 bat cases were registered in the states of Baja California Sur, Jalisco, and Guerrero. Furthermore, the Agriculture Department reported an outbreak of 233 cases of cattle paralytic rabies transmitted by vampire bats.…”
Section: Mexicomentioning
confidence: 99%
“…Several countries in the Americas have used the variation in partial N-gene stretches to describe RABV diversity associated with domestic and wild animals at improved resolutions not previously attained by monoclonal antibody typing ( Velasco-Villa et al, 2017 ). Over the last three decades, genetic typing with partial N-gene sequences has demonstrated not only to be a more sustainable technology to continue monitoring rabies in wildlife, but also to follow up on dog rabies elimination efforts by defining geographically circumscribed dog-maintained rabies foci ( Favoretto, et., 2006 ; Paez et al, 2007 ; Carnieli et al, 2013 ; Garces- Ayala et al, 2017 ; Jaramillo-Reyna et al, 2020 ). However, one technical limitation of this approach is that phylogenetic reconstructions depicting putative lineages show low branch support values due to a limited number of informative sites compared to the large number of sequences analyzed at once ( Guindon et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Continued surveillance of dog-maintained RABV lineages using partial, complete N-gene, or complete genome sequences was critical to validate Mexico free of human rabies mediated by dogs. Thus far, Mexico has had sustained RABV surveillance using partial N-gene sequences, reserving genomic approaches only for cases that require a higher level of resolution, such as persistent rabies foci on its border with central America ( Garcés-Ayala et al, 2017 ). Applying a similar framework to Ethiopia, we observed that sequences pertaining to different lineages presented pairwise genetic distances greater than 1.3% ±0.4%, and that average pairwise genetic distances within-lineages increase as the spatial-temporal sampling increased across regions, consistent with studies in other African countries ( Brunker et al, 2015 , Bourhy, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%